PENGARUH PRINSIP GOOD GOVERNANCE TERHADAP PENGELOLAAN KEUANGAN DESA DI KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - Ines Saraswati Machfiroh; Yuli Fitriyani; Yasir Hadiani (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2025)
Village financial management is supported by several principles, namely transparency, accountability, participation, responsiveness, and competence. This study aims to determine the effect of good governance principles (transparency, accountability, participation, responsiveness, and competence) as independent variables on village financial management as the dependent variable in Takisung District, Tanah Laut Regency. The population in this study consists of village officials working in village and sub-district offices within the Takisung District area, with a sample of five village and sub-district offices and a total of 40 respondents. This study employs a quantitative approach with data collection techniques using questionnaires. Data analysis was carried out using descriptive statistics, data quality tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The results show that both partially and simultaneously, transparency, accountability, participation, responsiveness, and competence have a significant effect on village financial management. The R-Square value of 0.979 or 97.9% indicates that these five principles of good governance dominantly determine the effectiveness of village financial management, while the remaining 2.1% is influenced by other factors outside this study. These findings imply that the consistent implementation of good governance principles can enhance accountability and efficiency in village financial management.